2022
DOI: 10.4028/p-ytr30y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive Polymer Composite Based on Graphite-Filled Immiscible Polyolefin/Epoxy Blends

Abstract: Conductive polymer composites (CPCs) based on polypropylene (PP)/epoxy (EP) and high-density polyethylene (HDPE)/EP blends filled with synthetic graphite (SG) were produced and characterized to explore their potential for high electrical conductivity applications. The polymer blends were chosen as matrices due to their immiscibility and potential to enable co-continuous morphology formation and preferential distribution of filler, which allows formation of maximized conducting networks. In-plane and through-pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, a number of studies have been reported that electrically conducting composite materials based on polymer blends can achieve high electrical conductivities with lower filler contents than a single-component polymer. 25,26 This is caused by creating double percolation because the conductive filler is heterogeneously distributed within one phase of the blended matrix or at the interface between polymer blends. Recently, Lencar et al designed a novel two-step mixing approach to pre-localize MWCNTs within the polyethylene phase, and subsequently allow them to migrate into the thermodynamically favored poly(vinylidene fluoride) phase.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a number of studies have been reported that electrically conducting composite materials based on polymer blends can achieve high electrical conductivities with lower filler contents than a single-component polymer. 25,26 This is caused by creating double percolation because the conductive filler is heterogeneously distributed within one phase of the blended matrix or at the interface between polymer blends. Recently, Lencar et al designed a novel two-step mixing approach to pre-localize MWCNTs within the polyethylene phase, and subsequently allow them to migrate into the thermodynamically favored poly(vinylidene fluoride) phase.…”
Section: Introductionmentioning
confidence: 99%